Activation of the GABAB Receptor Prevents Nicotine-Induced Locomotor Stimulation in Mice - Lobina, Carla; Carai, Mauro A.; Froestl, Wolfgang; Mugnaini, Claudia; Pasquini, Serena; Corelli, Federico; Gessa, Gian Luigi; Colombo, Giancarlo (Frontiers in Psychiatry, 2011)
Recent studies demonstrated that activation of the GABAB receptor, either by means of orthosteric agonists or positive allosteric modulators (PAMs), inhibited different nicotine-related behaviors, including intravenous self-administration and conditioned place preference, in rodents. The present study investigated whether the anti-nicotine effects of the GABAB receptor agonist, baclofen, and GABAB PAMs, CGP7930 and GS39783, extend to nicotine stimulant effects. To this end, CD1 mice were initially treated with baclofen (0, 1.25, and 2.5 mg/kg, i.p.), CGP7930 (0, 25, and 50 mg/kg, i.g.), or GS39783 (0, 25, and 50 mg/kg, i.g.), then treated with nicotine (0 and 0.05 mg/kg, s.c.), and finally exposed to an automated apparatus for recording of locomotor activity. Pretreatment with doses of baclofen, CGP7930, or GS39783 that did not alter locomotor activity when given with nicotine vehicle fully prevented hyperlocomotion induced by 0.05 mg/kg nicotine. These data extend to nicotine stimulant effects the capacity of baclofen and GABAB PAMs to block the reinforcing, motivational, and rewarding properties of nicotine. These data strengthen the hypothesis that activation of the GABAB receptor may represent a potentially useful, anti-smoking therapeutic strategy.